1984
DOI: 10.1523/jneurosci.04-08-02051.1984
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-selective properties of inferior temporal neurons in the macaque

Abstract: Previous studies have reported that some neurons in the inferior temporal (IT) cortex respond selectively to highly specific complex objects. In the present study, we conducted the first systematic survey of the responses of IT neurons to both simple stimuli, such as edges and bars, and highly complex stimuli, such as models of flowers, snakes, hands, and faces. If a neuron responded to any of these stimuli, we attempted to isolate the critical stimulus features underlying the response. We found that many of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

67
851
3
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,320 publications
(933 citation statements)
references
References 22 publications
67
851
3
2
Order By: Relevance
“…While the visual cortex of BNNs may use quite different learning algorithms, its objective function to be minimised may be quite similar to the one of visual ANNs. In fact, results obtained with relatively deep artificial DBNs (Lee et al, 2007b) and CNNs (Yamins et al, 2013) seem compatible with insights about the visual pathway in the primate cerebral cortex, which has been studied for many decades (e.g., Hubel and Wiesel, 1968;Perrett et al, 1982;Desimone et al, 1984;Felleman and Van Essen, 1991;Perrett et al, 1992;Kobatake and Tanaka, 1994;Logothetis et al, 1995;Bichot et al, 2005;Hung et al, 2005;Lennie and Movshon, 2005;Connor et al, 2007;Kriegeskorte et al, 2008;DiCarlo et al, 2012); compare a computer vision-oriented survey (Kruger et al, 2013).…”
Section: Consequences For Neurosciencementioning
confidence: 80%
“…While the visual cortex of BNNs may use quite different learning algorithms, its objective function to be minimised may be quite similar to the one of visual ANNs. In fact, results obtained with relatively deep artificial DBNs (Lee et al, 2007b) and CNNs (Yamins et al, 2013) seem compatible with insights about the visual pathway in the primate cerebral cortex, which has been studied for many decades (e.g., Hubel and Wiesel, 1968;Perrett et al, 1982;Desimone et al, 1984;Felleman and Van Essen, 1991;Perrett et al, 1992;Kobatake and Tanaka, 1994;Logothetis et al, 1995;Bichot et al, 2005;Hung et al, 2005;Lennie and Movshon, 2005;Connor et al, 2007;Kriegeskorte et al, 2008;DiCarlo et al, 2012); compare a computer vision-oriented survey (Kruger et al, 2013).…”
Section: Consequences For Neurosciencementioning
confidence: 80%
“…Micro-electrode studies in macaque have used simple luminance-defined, geometrical constructs and found neurons in IT that fired preferentially for related shapes (Desimone et al, 1984;Gallant et al, 1996;Gross et al, 1972;Tanaka et al, 1991) in a cue-invariant fashion (Sary et al, 1993). Neurons that are selective for object shape have also been found in V4 (Gallant et al, 1996;Pasupathy and Connor, 2002).…”
Section: Tuning For Shapementioning
confidence: 99%
“…Since in the monkey temporal lobe, not only facebut also hand-responsive cells have been reported (31,32), pictures of hands, faces, and objects were presented to the same patients with subdural electrodes (16). Over the sites where face-specific responses were expected, hands did not induce significant differences.…”
Section: Perception Of Human Faces As Compared With Face Parts and Otmentioning
confidence: 99%